Health policy analysis of the non-implementation of HPV vaccination coverage in the pay for performance scheme in France. (25th September 2018) - Ohannessian, Robin; Constantinou, Panayotis; Chauvin, Franck
Abstract: Background: The French National Cancer Control Plan (NCCP) launched in 2014 set the objective to improve human papillomavirus (HPV) vaccination coverage (VC). The NCCP included a measure to integrate a VC indicator in the pay for performance (P4P) scheme for general practitioners (GPs), which was not implemented. The objective of the study was to analyse the reasons for non-implementation of this measure, using the health policy analysis framework. Methods: The policy from proposal to non-implementation of the HPV VC indicator into the P4P scheme was analysed through the actors involved, the content of the measure, the contextual factors and the processes of policy-making. Results: The actors were the Ministry of Health (MOH) and National Cancer Institute as policy-makers, the public health insurance as an indirect target, and GPs as direct targets. The content of the policy was not evidence-informed and was not included into the NCCP preparation report. The context included vaccine hesitancy and ethical concerns from GPs in opposition with MOH. The process involved a diversity of stakeholders with a complex governance and no strict monitoring of the measure. Conclusions: Complex vaccination policy governance associated with a non-evidence-informed policy content and an unfavourable context may have been the reasons for the policy failure.